Exploring the kinetic selectivity of drugs targeting the β1‐adrenoceptor. Issue 4 (28th June 2022) - Sykes, David A.; Jiménez‐Rosés, Mireia; Reilly, John; Fairhurst, Robin A.; Charlton, Steven J.; Veprintsev, Dmitry B.
Abstract: In this study, we report the β1 ‐adrenoceptor binding kinetics of several clinically relevant β1/2 ‐adrenoceptor (β1/2 AR) agonists and antagonists. [ 3 H]‐DHA was used to label CHO‐β1 AR for binding studies. The kinetics of ligand binding was assessed using a competition association binding method. Ligand physicochemical properties, including logD7.4 and the immobilized artificial membrane partition coefficient ( K IAM ), were assessed using column‐based methods. Protein Data Bank (PDB) structures and hydrophobic and electrostatic surface maps were constructed in PyMOL. We demonstrate that the hydrophobic properties of a molecule directly affect its kinetic association rate ( k on ) and affinity for the β1 AR. In contrast to our findings at the β2 ‐adrenoceptor, K IAM, reflecting both hydrophobic and electrostatic interactions of the drug with the charged surface of biological membranes, was no better predictor than simple hydrophobicity measurements such as clogP or logD7.4, at predicting association rate. Bisoprolol proved kinetically selective for the β1 AR subtype, dissociating 50 times slower and partly explaining its higher measured affinity for the β1 AR. We speculate that the association of positively charged ligands at the β1 AR is curtailed somewhat by its predominantly neutral/positive charged extracellular surface. Consequently, hydrophobic interactions in the ligand‐binding pocket dominate the kinetics of ligand binding. In comparison at the β2 AR, a combination of hydrophobicity and negative charge attracts basic, positively charged ligands to the receptor's surface promoting the kinetics of ligand binding. Additionally, we reveal the potential role kinetics plays in the on‐target and off‐target pharmacology of clinically used β‐blockers. Abstract : Exploring factors influencing drug binding and receptor selectivity at β‐adrenergic receptors.